Significant Increase of Prostaglandin E‐Major Urinary Metabolite in Male Smokers: A Screening Study of Age and Gender Differences Using a Simple Radioimmunoassay. Issue 1 (27th December 2013) - Okayasu, Isao; Ohnishi, Hiromitsu; Sarandi, Istvan; Shojima, Junko; Komatsu, Junko; Oritsu, Masae; Sasabe, Masataka; Nanami, Kaori Okayasu; Matsuura, Masaaki; Azumi, Jun‐ichi; Ito, Satoru; Fujiwara, Mutsunori
<x xml:space="preserve">Abstract</x> Background For the assessment of inflammatory status, we have developed a simple, reliable radioimmunoassay (RIA) of prostaglandin E‐major urinary metabolite (PGE‐MUM), which remains stable in urine after it is metabolized. Using this method, we conducted a screening study to compare standard values of PGE‐MUM to serum C‐reactive protein (CRP) levels in health check volunteers. Methods PGE‐MUM (micrograms per gram creatinine) was measured in normal urine samples obtained from 797 samples in volunteers for health check, using a newly developed RIA, and analyzed in relation to age, gender, smoking, and drinking habits. Results were compared to serum CRP. Results PGE‐MUM was significantly higher in males than in females. It was significantly higher in smoking males, compared to males who had never smoked (nonsmokers), particularly in those above 40 years of age. In nonsmokers, PGE‐MUM declined in males with advancing age, while it rose in females. Although PGE‐MUM reflected current smoking status, independent of smoking index (SI), serum CRP indicated both current and former smoking condition, rather dependent upon SI. Conclusions PGE‐MUM increases in smokers, as suggested by possible inflammatory injury of pulmonary tissue. This RIA method for PGE‐MUM may be thus a sensitive and reliable biomarker for current inflammation, different from serum CRP.